2020
DOI: 10.46244/geej.v7i2.1019
|View full text |Cite
|
Sign up to set email alerts
|

Adjective and Noun Clause Lexical Density in an English Textbook for Senior High School Students

Abstract: This paper analyzed the lexical density of the adjective and noun clauses in an English textbook for senior high school students in Indonesia. It aimed to discover whether or not the textbook was suitable for the students in terms of lexical density. The researchers employed a content analysis approach to analyze data. There were 116 sentences, containing adjective and noun clauses, which were investigated. The researchers implemented the lexical density theory and the lexical density indicators to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In other words, higher levels of texts do not necessarily guarantee higher lexical density indexes. Prawinanto and Bram (2020) explored lexical density in an English Textbook for senior high school students by focusing on adjective and noun clause appearance. Results showed that there were three lexical density levels found in those adjective and noun clauses.…”
Section: Lexical Densitymentioning
confidence: 99%
“…In other words, higher levels of texts do not necessarily guarantee higher lexical density indexes. Prawinanto and Bram (2020) explored lexical density in an English Textbook for senior high school students by focusing on adjective and noun clause appearance. Results showed that there were three lexical density levels found in those adjective and noun clauses.…”
Section: Lexical Densitymentioning
confidence: 99%